The use of SDR finance for collectively agreed purposes - TRIFFIN, R. (PSL Quarterly Review, 2014)
The international debate on international monetary reform that began in the early 1960s ha proceeded with a logic and consistency unparalleled in other areas of international relations. The SDR agreement, in particular, constitutes a major breakthrough, deemed until recently to be totally utopian and unattainable, toward a rational management of the international monetary system. The agreement as it now stands, however, still fails to deal adequately with the objective of an allocation of SDRs serving collectively agreed purposes rather than unilaterally decided national policies, potentially disruptive of equilibrium and/or obnoxious to the countries called upon to finance them through forcible SDR accumulation. The author argues that internationally created reserves should be used for internationally agreed upon objectives, rather than the blind financing of national policies that may be financially, economically or politically disruptive. JEL: E42, F33